Fun and function : camp as guiding spirit in design workflow : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand - Jenner, Nadia (Massey University, 2022)
The capitalist framework gives rise to conditions that prompt labourers – in this case, designers of artefacts and images – to adopt efficient occupational formulae in order to rapidly produce design as a decontextualised commodity. This pre-existing drive for workplace efficiency has been exacerbated by a wider economic shift into competitive, fragmented work structures. Through the pursuit of acceptable design which is not ‘in bad taste’ (read; gaudy, garish, controversial), a new aesthetic sensibility emerges; one which prioritises safe digestibility in order to garner commercially advantageous universal appeal. This homogenisation of design output is a visible symptom, but the core issue stemming from these conditions is the alienation and isolation between designers, artefacts, and clients, as a result of accelerated efficient design practices. The preliminary research uses a postmodernist lens to establish the framing of the visual outcomes of efficient design workflows as kitsch. By transcending the obsolete binaries of ‘high’ and ‘low’ art, kitsch can be harnessed as a value neutral way of framing of visual communication design. It is through a renewed understanding of kitsch, that camp – a related but distinct concept – is revealed as a possible means of intervention. This unites a core concept – kitsch – with a mode of critique which aligns with my primary aim for this project – prioritising the heart and joy in design practice. Through this project I have honed a design philosophy which responds to these conditions, and provides designers who have efficient design workflows with an opportunity for reflection and connection, encouraging their personal reshaping and reimagining of their own design workflow. Camp is a culturally rich concept which can operate as both an alternate mode of seeing, and a form of cultural critique. Here, camp is employed as a form of immanent critique, utilising devices such as stylistic exaggeration, theatricality, and ironic juxtaposition in order to illuminate possibilities for radical intervention in design workflows. Efficient design workflows are held as a focal point, forming a grounded basis of immanent critique. This exploration culminates in an evaluation of how its resultant design philosophy may act as an intervention in efficient design practices, with consideration given to its viability within the context of the workplace.
Keywords: 330304 Design history, theory and criticism